Spectral analysis of sine-sweep vibration: A fatigue damage estimation method. (August 2021) - Palmieri, M.; Cianetti, F.; Zucca, G.; Morettini, G.; Braccesi, C.
Highlights: A frequency domain approach for the evaluation of fatigue life in case of Sine-Sweep test is proposed. The proposed method is compared with classical time domain approach supplying accurate results in terms of fatigue damage. The proposed method can solve multiaxial stress state reducing it into an equivalent uniaxial stress. The computational time needed with the proposed method for the evaluation of fatigue damage is 16 time lower if compared to time domain method. Abstract: The use of frequency methods for the estimation of fatigue life of mechanical components has almost supplanted the use of classical time domain methods due to their effectiveness about results and efficiency. Most of spectral methods are developed for random applications while other excitations, such as sine-sweep, are devoid of ad hoc methods. Given the countless advantages of spectral methods, this activity proposes a frequency domain method for fatigue life estimation for sine-sweep excitation. The proposed approach, tested on a simple structure, showed it can achieve the same results of a classical time domain approach but with a remarkable computational efficiency.